2015
DOI: 10.1093/cid/civ556
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Virological Outcomes of First-Line Antiretroviral Therapy for HIV-1 in Low- and Middle-Income Countries: A Systematic Review and Meta-analysis

Abstract: Among individuals retained on ART, virological suppression rates during the first 5 years of ART were high (>80%) and stable. Suppression rates in ITT analysis declined during 4 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
104
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 137 publications
(122 citation statements)
references
References 13 publications
12
104
2
1
Order By: Relevance
“…Subsequent sustenance of long-term and successful treatment outcomes depends primarily on achieving sustained viral suppression, supported by optimum life-long adherence [2]. Remarkably high levels of adherence have been reported in sub-Saharan Africa in comparison to western countries [3], but these findings contrast with those from other studies reporting increasing levels of patients with treatment failure [4,5], low retention [6] and high mortality rates [7]. Fewer studies have assessed adherence in long-term treated patients, despite the growing numbers as ART programs mature in the region [8–10].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent sustenance of long-term and successful treatment outcomes depends primarily on achieving sustained viral suppression, supported by optimum life-long adherence [2]. Remarkably high levels of adherence have been reported in sub-Saharan Africa in comparison to western countries [3], but these findings contrast with those from other studies reporting increasing levels of patients with treatment failure [4,5], low retention [6] and high mortality rates [7]. Fewer studies have assessed adherence in long-term treated patients, despite the growing numbers as ART programs mature in the region [8–10].…”
Section: Introductionmentioning
confidence: 99%
“…[6–7] As WHO targets were not available for Viral load suppression at 6 months , Namibia used WHO’s 12-month targets as international literature reflected similar viral load suppression rates at 6 and 12 months. [18] The targets utilize three performance classifications: red (poor performance, below desired level), amber (fair performance, not yet at desired level), and green (excellent performance, achieving desired level). The targets also allow for a “grey” classification if a site does not have data available to monitor a specific EWI.…”
Section: Methodsmentioning
confidence: 99%
“…This is of importance, since although most ART regimens applied in the developed world do not include NRTIs, the great majority of HIV-infected patients are treated in the developing world (such as Africa) with regimens in which NRTIs are part of most first line therapies for ART 64,65. Interestingly, a recent study suggested that exposure to didanosine (even if later replaced) is a risk factor for liver fibrosis in HIV, although the mechanisms behind this effect are unclear 66.…”
Section: Mitochondrial Dysfunction and Toxicitymentioning
confidence: 99%